Solid Pseudopapillary Neoplasm of the Pancreas: Unfolding an Intriguing Condition - Manuel António Alves Cruz (Karger Publishers, 2021)
Pancreatic cancer is one of the most lethal malignant neoplasms, with a 1-year survival rate after diagnosis of 24%, and a 5-year survival rate of only 9%. While this illustrates the behavior of its main histologic type – ductal adenocarcinoma, there are other histologic subtypes of pancreatic cancer that can harbor excellent prognosis. Solid pseudopapillary neoplasm, described as a rare low-grade malignant neoplasm by the World Health Organization, is the best example of that, having an overall 5-year survival rate of about 97%. Not only the prognosis, but everything about this entity is unique: its histogenesis, epidemiology, presentation, imaging characteristics, cytology features, immunohistochemical profile, and treatment. This explains the urge to improve our understanding about this entity and thus our ability to accurately recognize and manage it. Having this in mind, this article aims to summarize the most relevant topics regarding this entity.